To switch or not? Effects of spokes-character urgency during the social app loading process and app type on user switching intention - Zhang, Ning; Hu, Hsin-Li; Tso, Scarlet H.; Liu, Chunqun (Frontiers in Psychology, 2023)
Users of mobile phone applications (apps) often have to wait for the pages of apps to load, a process that substantially affects user experience. Based on the Attentional Gate Model and Emotional Contagion Theory, this paper explores the effects of the urgency expressed by a spokes-character’s movement in the loading page of a social app the app type on users’ switching intention through two studies. In Study 1 (N = 173), the results demonstrated that for a hedonic-oriented app, a high-urgency (vs. low-urgency) spokes-character resulted in a lower switching intention, whereas the opposite occurred for a utilitarian-oriented app. We adopted a similar methodology in Study 2 (N = 182) and the results showed that perceived waiting time mediated the interaction effect demonstrated in Study 1. Specifically, for the hedonic-oriented (vs. utilitarian-oriented) social app, the high-urgency (vs. low-urgency) spokes-character made participants estimate a shorter perceived waiting time, which induces a lower user switching intention. This paper contributes to the literature on emotion, spokes-characters, and human–computer interaction, which extends an enhanced understanding of users’ perception during loading process and informs the design of spokes-characters for the loading pages of apps.